Assessing reported condom use among female sex workers in southern India through examination of condom availability. (18th February 2010) - Bradley, Janet; Moses, Stephen; Blanchard, James F; Rajaram, S; Ramesh, B M; Verma, Supriya; Alary, Michel
Abstract : Objectives: A key indicator of success of HIV prevention programmes is the number of female sex worker (FSW) sex acts protected by condoms. This measure usually relies on FSW reports, which may be biased. We examined condom availability data in five Karnataka districts to estimate the proportion of FSW sex acts potentially protected by condoms. Methods: Financial, programme, population, condom and contraceptive data were obtained from governmental and non-governmental sources, surveys and HIV prevention programmes. Sexual behaviour data were obtained from general population and FSW surveys. We examined four scenarios in a sensitivity analysis, each one assuming different proportions of available condoms that might have been used by sex workers. Results: Possible condom use rates for all FSW sex acts ranged from 3%–36% in 2004 to 56%–96% in 2008. The two most realistic scenarios that discounted the number of private sector condoms that might have been bought for sex acts other than with FSWs showed that 16–24% of FSW sex acts could have been protected by condoms in 2004 rising to 77–85% in 2008. Conclusions: These data suggest that condom availability in these Karnataka districts in 2004 was low in relation to the number of FSW sex acts, but rose substantially over the ensuing 4 years. Condom availability data can be useful for triangulation with other available data, such as self-reported condom use, to provide a range of possibilities regarding the number of FSW sex acts protected by condoms.